Sistematización de experiencias en gestión documental en el departamento de tecnologías de información y comunicación en la Universidad Técnica de Cotopaxi - Caisalitin Cunalata, Digna Carolina (2019)
The management is a set of technology, standards, and techniques that allow the institution to manage documents properly, allowing high performance, efficiency, and file functionality. Today, to achieve efficient documentary management in an organization, it is essential to have an information system that allows the management, storage, and preservation of all those institutional documents that are vital for management. This research work entitled "Systematization of experiences in document management at the Department of Information Technology & Communication of the Technical University of Cotopaxi" aims to analyze and identify the documentary management critically in the Digital Systems of headquarters Campus DoITC at Technical University of Cotopaxi, to provide possible solutions so that the information is handled correctly and appropriately. One of the first tasks is to obtain real and accurate information, related to the current situation of the dependency according to the matrix of registration of weekly activities, the records that will help to give viability and possible solutions to the objectives proposed in the project. Based on this, an informative document management system is proposed that allows dissipating, ordering and archiving all information that arrives the Department of Information & Communication Technologies of the Technical University of Cotopaxi. Finally, the conclusions of the project are presented analyzing the importance of documentary management as an indispensable resource in each company and institution, which allows organizing, document, and archiving all correspondence made by the different departments.